Pemberdayaan Ekonomi Mikro Berbasis Ibu Rumah Tangga di Desa Tanjung Lor Pacitan - Maryono Maryono; Mukodi Mukodi; Yeni Utami (LPPM STKIP PGRI Pacitan, 2016)
The purpose of this study to describe the housewife-based economy in Pakis, Tanjung lor, Pacitan through training on making plastic flowers. The reasons were that easy to make, able to be sold, having high value, usually interesting among children, youth, or adult women, the cheap materials and easy to obtain, having many benefits. This program aimed at creating economic stability in Pakis hamlet, the additional income for young housewife (young couple) in Pakis. The program was implemented by the following steps, ie observation, analysis of finding from the field, the field needs analysis, program planning, program implementation, and evaluation of programs. The results of this study uncovered that mothers, who initially had not known what plastic flowers were and how to make it, had already been able to make beautiful flowers made from plastic. The obtained creativity could be both developing creativity and be creating opportunities for entrepreneurship specifically for those having no job and intentionally worked as the housewife. Finally, that could also develop the further micro-economy for society.